Bentuk dan Nilai Baru dalam Kreativitas Penciptaan Komposisi Musik Gender Wayang “Tipat Taluh” - Bhumi, I Made Bayu Puser; Ardini, Ni Wayan; Yudarta, I Gede (Bali Membangun Bali: Jurnal Bappeda Litbang, 2024)
Purpose: This research was conducted to show that there are many dimensions of creativity that can develop in the form of creating new Gender Wayang works. This can be observed through one of Gender Wayang's new works entitled “Tipat Taluh”. Research methods: The research method used is a qualitative research method. Data collection was carried out by observation, interviews, and document studies. Results and discussion: Departing from in-depth analysis processes, the result was that “Tipat Taluh”'s work is a new musical composition for Gender Wayang where the big idea is based on philosophical thoughts which have implications for the discovery of a new form and method of composition for Gender Wayang. With the concept of balance and simplicity of “Tipat Taluh” (egg-shaped ketupat), Gusti Komin Darta (composer) transformed these concepts into a new work on Gender Wayang. The updates carried out clearly have a tendency towards processing musical patterns as well as a new system of forming intertwining (kotekan). Implications: The balance of aspects of preservation and development of Gender Wayang will have a positive impact if both are in balance, preservation through contestation, while development by fostering the creation of new works on Gender Wayang.